Analisis Kelulusan Mahasiswa Menggunakan Algoritma C.45 - Risnawati Risnawati (Jurnal Mantik Penusa, 2018)
The development of computer technology is very much utilized in education. This technological advancement should be able to affect students in completing their cultivation. however, the number of students who do not pass in time makes the problem for both the student and the academic. Therefore, the academic campus is expected to help students in providing input, especially to new students to know the factors that inhibit and support the graduation of students. Academic parties actually have a very large data warehouse related data and student graduation that has not been used optimally. Therefore, existing data warehouses can be extracted to obtain useful information in analyzing student graduation factors. The method that researchers use is the method of Classification with Algorithm C.45 which is a branch in data mining. Through the method of Classification Algorithm C.45, researchers will compare each attribute that affects student graduation. Based on the research process conducted there are 4 results analysis on the relationship of attributes that affect student graduation. The four rules can be an input for students and academics in determining the right strategy in overcoming graduation problems for students. Keywords: Graduation, Analysis, Student, Data Mining, Algorithm C.45